In situ morphometric survey elucidates the evolutionary systematics of the orchid genus Gymnadenia in the British Isles. Issue 6 (18th August 2021) - Bateman, Richard M.; Rudall, Paula J.; Denholm, Ian
Abstract : Circumscriptions of both the genus Gymnadenia and the 11–27 species that it contains are highly controversial. These Eurasian terrestrial orchids are nectar-rewarding and pollinated primarily by Lepidoptera. Opinions expressed on the number of species occurring in the British Isles range from one to four, though there exists broad agreement that at least three recognizable, ecologically differentiated taxa are widespread. Here, we use a large-scale morphometric survey of these supposedly 'cryptic' taxa to determine whether phenotypic differentiation exists alongside their documented genotypic and ecological differentiation, seeking the most diagnostic morphological characters. Ten Gymnadenia plants were measured in each of 29 populations that encompassed the entire taxonomic range and geographic distribution of the genus within the British Isles. Results were subjected to detailed multivariate and univariate analyses, and interpreted in the context of molecular phylogenies, including a bespoke Europe-wide nrITS phylogeny that includes 17 plants sampled across Britain and Ireland. Floral micromorphology was investigated through scanning electron microscopy. Ecotypes occurring respectively in calcareous grasslands ( G. conopsea s.s.), acid heaths ( G. borealis ) and calcareous to neutral marshes ( G. densiflora ) are subtly but reliably distinct, both morphologically and molecularly, though locally their morphological distinctiveness is somewhat weakened by the occurrence of infrequent populations in dune slacks and chalk downs that are intermediate in phenotype between the grassland and marsh ecotypes ('subsp. cf. friesica '). A polythetic taxonomic key emphasizes the characters and character-state ranges that are demonstrably the most diagnostic. Given that they are reliably genetically differentiable, and individuals can be distinguished with ∼85% confidence using morphological characters such as flower dimensions, depth of flower colour, and leaf number and size, we uphold our previous arguments that the three ecotypes merit species-level recognition. In the continued absence of field sequencing devices, identification is best attempted through quantitative examination of morphology focused at the population level, rejecting records of isolated plants. Despite their strong morphological similarity, genus-wide molecular data show that the British species are not each other's closest relatives. Gymnadenia borealis remains one of only three orchid species putatively endemic to the British Isles.